Pengoptimalan Perpustakaan Sekolah SMP Batik Program Khusus Surakarta melalui Aplikasi SLiMS - Eko Purnomo; Zainal Arifin (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2021)
The school library is one of the crucial supporting facilities in learning. This study aims to describe the optimization of school libraries through the SLiMS application. This research is a qualitative research with the type of descriptive research. The data source in this study is the SLiMS application while the data is the use of the SLiMS application at the Surakarta Special Program Batik Junior High School for optimizing the school library. Data collection techniques are content analysis, observation and note-taking techniques. The data analysis method in this study uses an interactive model of Milles and Hubberman. The results of the study show that the optimization of the school library can be done by using the SLiMS application. This application can be used by librarians to manage school libraries. The optimizations are (1) arranging library administration for the Surakarta Special Program Batik Middle School, (2) classifying the books in the library, and (3) cataloging and attaching labels to books. With this optimization, it is hoped that it will support student achievement and higher interest in library.